Factors Related to Anxiety Events in Parkinson's Patients in Dr. M Djamil Padang - Kurniawan, Yoga Setia; Yuliarni Syafrita; Restu Susanti (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Introduction : Anxiety is one of the most non-motorized symptoms in patients with Parkinson's which greatly affects the quality of life, but in clinical practice it is often neglected. Anxiety in patients with Parkinson's can accelerate motor deterioration / disability and also increase mortality. Methods: This cross-sectional study was conducted at the Neurology polyclinic Dr. M Djamil Padang from July to December 2020 in patients who had been diagnosed with Parkinson's Disease (PD) by excluding secondary Parkinson's and a history of stroke. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS). The research subjects were 60 people. Univariate analysis to present baseline characteristics and bivariate tests assessed factors associated with anxiety and the relationship between variables. A p value <0.05 was considered statistically significant. Results: Most of the subjects were male (55%) with a mean age of 58.05 Â± 9.7 years and disease duration of 6.35 Â± 5.29 years. By examining the Hamilton Anxiety Rating Scale (HARS), it was obtained 38.3% of Parkinson's sufferers with anxiety. There is a significant relationship between marital status, duration of illness and degree of disease with the incidence of anxiety (p <0.05) and there is no significant relationship between age and sex with the incidence of anxiety in patients with Parkinson's. Conclusion: There is a significant relationship between marital status, duration of illness and degree of disease with the incidence of anxiety in patients with Parkinson's and there is no relationship between age and sex with the incidence of anxiety in patients with Parkinson's.